Effects of conservation tillage on soil water content in northern arid regions of China. In Chinese - Jiantao, D.; Wenqing, H.; Nangia, Vinay; Changrong, Y.; Ahmad, Mobin-ud-Din; Shuang, L.; Qin, L. (2008)
Soil water content is the key factor that affect the agriculture production in northern arid regions of China. It is helpful to select proper tillage methods and improve water productivity based on the study of soil water content changing. Soil water content, water balance and water use efficiency were simulated and checked used the DSSAT model based on two-year field experiment. The results show that in dry year the soil water content of conservation tillage is higher than the conventional tillage, RMSE is 0.025-0.063. In dry year, and the largest decrease of soil water storage is conventional tillage (144.6 mm), and the same in normal year (46.1 mm). Water use efficiency in dry year is 1.52-1.78 kg/m3, the largest is no tillage with residue cover treatment, in the normal year is 1.70-1.71 kg/m3. The differences between different treatments are not obvious. The results provide theoretical foundation for the research of effects of conservation tillage on soil water in the field.